Development of Smart Alarm based Android - AZEMAN, AZREL AIMAN (Applied Information Technology And Computer Science, 2022)
Alarms are a very important tool to most walks of life now, especially for managing the timing of their activities. Alarms are also easy to use and are available in all smartphones as well as on alarm clocks. In this project the ‘Smart Alarm’ application was developed. The prototype method is used as the methodology of this application. Android Studio software is used in application development. Previously, no application had features such as creating notes and alarms in one application. This makes it difficult for users as they need an alarm app that has various features such as notes, prayer time reminders and surrounding weather conditions. So the ‘Smart Alarm’ Application is built to make it easier for users to manage their time/and daily schedule. In this application, the user only needs to set the alarm as appropriate. In this application, methods to close the alarm are introduced i.e. simple mathematical solutions, shake, hold buttons and text. In addition, there are features such as making notes and reminders of prayer times along with the surrounding weather conditions.